Entrepreneurial Self-Efficacy Mediates the Impact of the Post-pandemic Entrepreneurship Environment on College Students’ Entrepreneurial Intention - Zhang, Jiping; Huang, Jianhao (Frontiers in Psychology, 2021)
The mechanism of how the COVID-19 global pandemic has affected the entrepreneurial intentions of college students remains unknown. To investigate the impact of the entrepreneurial environment on entrepreneurial self-efficacy and entrepreneurial intentions in the post-pandemic era, 913 college students were invited to complete a questionnaire. The data were analyzed with structural equation models. The conclusions revealed by the questionnaire are as followed: college students have retained some entrepreneurial intention in the post-pandemic era; the factors influencing the entrepreneurial intention include sex, family entrepreneurial history, major, and education background; and entrepreneurial self-efficacy can play a major role to mediate the impact caused by the post-pandemic entrepreneurial environment on entrepreneurial intentions. The research conclusions provide important insights to improve college students’ entrepreneurial intentions in the post-pandemic environment.